Effect of seed treatments using plant growth regulators on wheat (Triticum aestivum L.) seedling establishment, growth, seed yield and quality - Singh, Rajiv K.; Agarwal, D. K.; Tiwari, T. N.; Ram, Hardev; Prasad, S.R.; ., Renu (Annals of Agricultural Research, 2016)
A pot experiment was carried out during Rabi season of 2012-13 at research farm of ICAR-Directorate of SeedResearch, Mau, Uttar Pradesh. Growth, seed yield, seed quality parameters and germination of three wheatvarieties viz; HD 2733, PBW 550 and PBW 502 were studied.The wheat seeds were soaked in different solutionsof 100 ppm concentration of gibberellic acid (GA3sodium salt prior to planting. Hydro-primed and control seeds were also taken. The results of the study showedsignificant differences in growth, seed yield and seed quality parameters among the wheat varieties and differentgrowth regulator concentrations used. Seeds treated with 100 ppm GA3increase in plant height, number of tillers/plant, spike length, spike weight, number of seed/spike, test weight,seed yield and harvest index than the rest of treatments. Seeds pre-soaked in distilled water responded poorly.Significant improvement in the seed quality parameters viz, germination %, seedling length, seedling dry weightand vigour index I and II were recorded for100 ppm GA3 over the rest of treatments. Among the varieties PBW502 recorded significantly higher values for plant height, number of tillers/plant, spike length, spike weight,number of seeds/spike, seed weight/spike, test weight, seed yields, harvest index and seed quality parametersas compared to PBW 550 and HD 2733. The results emphasized that pre-sowing seed treatment of wheat seedswith GA3and IAA could significantly enhance the germination %, seedling length, seedling dry weight, vigourindex I and II.), indoleacetic acid (IAA), kinetin, 2,4-D amine salt and 2,4-D, IAA and kinetin showed significant